Evidence-Based Clinical Efficacy of Leukocyte and Platelet-Rich Fibrin in Maxillary Sinus Floor Lift, Graft and Surgical Augmentation Procedures - Damsaz, Mohamadamin; Castagnoli, Consuelo Zumarán; Eshghpour, Majid; Alamdari, Daryouosh Hamidi; Alamdari, Aida Hamidi; Noujeim, Ziad Eva Fouad; Haidar, Ziyad Samir (Frontiers in Surgery, 2020)
Bone augmentation techniques have increasingly been indicated for re-creating adequate bone height and volume suitable for dental implant sites. This is particularly applicable in the severely atrophic posterior maxilla where sinus perforation (ruptured Schneiderian membrane) is a very common complication and sinus floor elevation or lift is frequently considered a standard procedure. The augmentation of the maxillary sinus can be performed with or without grafting biomaterials. Herein, numerous biomaterials and bone substitutes have been proposed, primarily to sustain the lifted space. In addition, cytokines and growth factors have been used to stimulate angiogenesis, enhance bone formation as well as improve healing and recovery period, either as the sole filling material or in combination with bone substitute materials. Within such, is the family of autologous blood extracts, so-called platelet concentrates, which are simply the “product” resulting from the simple centrifugation of collected whole blood samples of the patient, immediately pre-surgery. Platelet-Rich Fibrin (PRF), a sub-family of platelet concentrates, is a three-dimensional (3-D) autogenous biomaterial obtained, without including anti-coagulants, bovine thrombin, additives, or any gelifying agents during the centrifugation process. Today, it is safe to say that, in implant dentistry and oral and maxillofacial surgery, PRFs (particularly, the pure platelet-rich fibrin or P-PRF and leukocyte and platelet-rich fibrin or L-PRF sub-classes) are receiving the most attention, essentially due to their simplicity, rapidness, user-friendliness/malleability, and cost-effectiveness. Whether used as the sole “bioactive” filling/additive material or combined with bone substitutes, the revolutionary second-generation PRFs have been very often associated with promising clinical results. Hence, this review aims to provide a 10-years update on the clinical effectiveness of L-PRF when applied/used as the “sole” biomaterial in maxillary sinus augmentation procedures. An electronic search using specific keywords for L-PRF and maxillary sinus augmentation was conducted in three main databases (PubMed-MEDLINE database, Google Scholar and Cochrane library) for the period between January 2009–February 2020. The quest yielded a total of 468 articles. Based on the pre-established strict inclusion/exclusion criteria, only seven articles were deemed eligible and included in the analysis. Surprisingly, of the 5 studies which used de-proteinized bovine bone mineral (DBBM) in combination with L-PRF, 60% acclaimed no significant effects and only 40% declared positive effects. Of the two articles which had used allogenous bone graft, 50% declared no significant effects and 50% acclaimed positive effects. Only one study had used L-PRF as the sole grafting material and reported a positive effect. Likewise, positive effects were reported in one other study using L-PRF in combination with a collagen membrane. Due to the heterogeneity of the included studies, this review is limited by the inability to perform a proper systematic meta-analysis. Overall, most of the published studies reported impressive results of L-PRF application as a grafting material (sole or adjuvant) in maxillary sinus augmentation and dental implant restorative procedures. Yet, distinct technical processing for L-PRF preparation was noted. Hence, studies should be approached with caution. Here in, in sinus lift and treatment of Schneider membrane, the formation of mature bone remains inconclusive. More studies are eagerly awaited in order to prove the beneficial or detrimental effects of PRFs, in general and L-PRFs, in specific; especially in their tissue regenerative potential pertaining to the promotion of angiogenesis, enhancing of cell proliferation, stimulation of cell migration and autocrine/paracrine secretion of growth factors, as well as to reach a consensus or a conclusive and distinct determination of the effect of leukocytes (and their inclusion) on inflammation or edema and pain; a call for standardization in PRFs and L-PRFs composition reporting and regimenting the preparation protocols.